Re-survey of the Whitehall study of London civil servants: changes in risk factors for cardiovascular disease during 29 years of follow-up. - Clarke, R; Breeze, E; Youngman, L; Sherliker, P; Bell, P; Shah, S; Shipley, M; Collins, R; Leon, D; Marmot, M; Fletcher, A (2000)
BACKGROUND: Substantial uncertainty persists about the relevance of blood pressure and cholesterol to the risk of cardiovascular disease in the elderly. OBJECTIVE: To investigate the determinants of cardiovascular risk in old age, and the relevance of such risk factors when recorded in middle and old age. METHODS: A re-survey in 1997 of 8537 survivors of a cohort of men who were originally examined in 1967-1970 when aged 40-69 years. RESULTS: Completed questionnaires were received from 7050 (82%) of the survivors, and blood pressure and blood samples from 5427 (64%). The response rate declined with increasing age, was inversely related to markers of socioeconomic status in 1967-70 and in 1997, and was lower in those who had been current smokers or had a higher blood pressure level in 1967-70. After excluding those with reported cardiovascular disease (25% of respondents), the mean levels of total cholesterol and apolipoprotein B were lower in older age groups, whereas apolipoprotein A1 levels did not vary much with age. Among those with risk factors recorded both in 1967-70 and 1997, the prevalence of smoking had declined by two-thirds (32% in 1970 and 12% in 1997), the prevalence of diabetes had increased (0.3% versus 4.5%), and the mean systolic blood pressure had increased by 16 mmHg (130 versus 146 mmHg), but the diastolic blood pressure had not changed materially (80 versus 81 mmHg), and the measured levels of total cholesterol had increased by 0.5 mmol/l (although that change may be artefactual). CONCLUSION: Follow-up of vital status in this cohort should permit an assessment of the relevance of risk factors recorded in middle and old age to cardiovascular disease in old age.